Goosed! - Wallace, Bill, 1947- (New York : Alladin Paperbacks, 2002)
When Jeff's girlfriend leaves a Labrador retriever puppy with his family for a week, his dog T.P. and cat Cord hope the energetic puppy does not stay any longer.
470
470
Accelerated Reader AR
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Bird dogs -- Fiction; Labrador retriever -- Fiction; Cats -- Fiction; Pets -- Fiction